The exploitation and environmental characteristics of diesel fuel containing rapeseed butyl esters - Makarevičienė, Violeta; Matijošius, Jonas; Pukalskas, Saugirdas; Vėgneris, Ričardas; Kazanceva, Irina; Kazancev, Kiril (Transport, 2013)
In an effort to consume fewer non-renewable resources and use primarily raw materials of biological origin in the production of biofuel, biomass-derived biobutanol can be used for transesterification of rapeseed oil. The study investigates the physical and chemical characteristics of rapeseed oil butyl esters (RBE) and 10%, 20% and 30% RBE-diesel composites. Characteristics of RBE and their composites with conventional diesel (D) are a little different from rapeseed oil methyl esters (RME) and their composites with D, while their basic characteristics comply with the requirements of European Standard EN 14214. Comparative tests in 4-stroke 4-cylinder 1Z type diesel engine of Audi-80 using 10–30% RBE and 10–30% RME compounds as fuels have been performed, and the results indicate that the biologically derived additives improved the energy characteristics of the engine but increased the fuel consumption compared to pure diesel. Increasing the bio-component concentration up to 30% in diesel and biodiesel fuel (RME and RBE) mixtures leads to complex improvements in the environmental impact compared to pure diesel; however, in the case of mixtures with RBE, slightly higher concentrations of CO2, HC and NOx were observed in engine exhaust gases compared to RME and D mixtures of analogical composition.First Published Online: 16 Jul 2013